2004
DOI: 10.1116/1.1815302
|View full text |Cite
|
Sign up to set email alerts
|

Phase measurement of reflection of EUV multilayer mirror using EUV standing waves

Abstract: Projection optics of an EUV lithography system consists of multilayer mirrors. Phase of the incident beam is shifted on reflection at the multilayer mirror [Y. Watanabe et al., Jpn. J. Appl. Phys. 30, 3053 (1991)]. If the phase shift at reflection of a multilayer is not well controlled, it becomes the cause of wavefront aberration. The phase shift depends on the incident angle and the wavelength of the beam. The phase shift is also dependent on the structure of the multilayer. Certain kinds of structural chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…39 As expected from the standing wave, the observed image contrast reverses as the incident light wavelength is tuned across the multilayer coating's Bragg peak. 38 Unexpected results include wide buried lines appearing as mere contours and of narrow lines as appearing significantly wider than expected. Lin et al attributed the broadening to the buried defect's depth ͑below the multilayer͒-at which the phase disturbance originates-being outside of the narrow depth of focus.…”
Section: Photoelectron Microscopymentioning
confidence: 87%
See 1 more Smart Citation
“…39 As expected from the standing wave, the observed image contrast reverses as the incident light wavelength is tuned across the multilayer coating's Bragg peak. 38 Unexpected results include wide buried lines appearing as mere contours and of narrow lines as appearing significantly wider than expected. Lin et al attributed the broadening to the buried defect's depth ͑below the multilayer͒-at which the phase disturbance originates-being outside of the narrow depth of focus.…”
Section: Photoelectron Microscopymentioning
confidence: 87%
“…1͑i͔͒. The sensitive correlation between the photoemission and the EUV reflective properties of multilayer mirrors ͑including phase͒ arises from the EUV standing wave and the field intensity near the surface, as discussed by Miyake et al 38 Lin et al demonstrated blank inspection and pattern imaging with the PEEM microscope.…”
Section: Photoelectron Microscopymentioning
confidence: 99%
“…Thus, many EUV reflectometers have been developed to assure mirror performance. [5][6][7][8][9][10][11][12][13] Reflectometers are required to perform highly precise wavelength and reflectance measurements, which must be reproducible to within 0.02 and 0.12%, respectively. 8) The development of high-power EUV sources is one of the critical issues for EUV lithography.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Tiwari et al 10 showed that the x-ray SW field can also be used to determine the concentration and location of various trace element contaminants embedded in different layers of the Mo/Si multilayer structure. Miyake et al 11 measured the wavelength dependencies of the reflectivity and the photoelectron signal. By using a model fit to experimental curves, they concluded that TEY is approximately proportional to the surface electric field intensity.…”
Section: Introductionmentioning
confidence: 99%